Neighborhood craftsmen: stories from Kanda's Gokura-Chou. 1 - Sakaue, Akihito, 1994- (Neighborhood Craftsmen, 2025)
Whether it's household goods or clothing or their very homes, the people of the Kanda neighborhood in the city of Edo depend on the expertise of local craftsmen. These artisans have years of experience perfecting their craft, but there's always room for them to learn and experiment, developing new techniques that will take their work to even greater heights. Step into the exquisitely illustrated workshops of a cooper, swordsmith, dyer, weaver, and plasterer and witness the traditional techniques on which modern Japan was built.